A transição demográfica no Brasil: a distribuição espacial, oportunidades e desafios - Reichert, Henrique (2015)
Amongst the different population regimes historically occurred, the modern demography transition period stands out. This population dynamic has been identified in Brazil since the 70 s decade, when several changes on the composition of the population and society happened. The works aims to analyze the demographic transition process in Brazil and its regional and social peculiarities, identifying socioeconomic opportunities and challenges. For that so, elements that originate this new population regime are investigated, moreover, a descriptive analysis about the demographic changes in Brazil was done, based on the IBGE projections. This way, it is identified that the Brazilian demographic bonus may end in 2022, showing a subsequent older population profile. In the Brazilian global process, it is verified the regional and social heterogeneity, coexisting both more advanced scenarios (south and southeast areas) and less ones (north and northeast areas) in the age transition. Also, it is verified that the economic growth seen since 1999 was directly connected with the increase on people of working age. However, it is not known until when it will be possible to count on this as an economic boost, once the increase of the number of people of working age is slowing down. Furthermore, a consideration is given to the need of improvement on the Brazilian productivity, a key element to sustain the growing of the elderly people. It may be considered that there are serious challenges to be overcome by the Brazilian economy, especially about the productive efficiency. On one side, the accumulation of physical capital faces macroeconomic and institutional obstacles and on the other side, the accumulation of human capital needs of educational provision of higher quality.